The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1080/15563650701226192
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic antidepressant poisoning: an evidence-based consensus guideline for out-of-hospital management

Abstract: American Association of Poison Control Centers, Washington, District of Columbia, USAA review of U.S. poison center data for 2004 showed over 12,000 exposures to tricyclic antidepressants (TCAs). A guideline that determines the conditions for emergency department referral and prehospital care could potentially optimize patient outcome, avoid unnecessary emergency department visits, reduce healthcare costs, and reduce life disruption for patients and caregivers. An evidencebased expert consensus process was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
83
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 240 publications
0
83
1
5
Order By: Relevance
“…In the two cases reported here, one with cardiac arrest and the other with severe cardiogenic shock, toxicity resolved after treatment with ILE therapy. Sodium bicarbonate has demonstrated efficacy in reversing QRS prolongation and cardiotoxicity following overdoses of tricyclic antidepressant [5] and other sodium channel blockers, but it was ineffective in these two cases.…”
Section: Case Discussionmentioning
confidence: 99%
“…In the two cases reported here, one with cardiac arrest and the other with severe cardiogenic shock, toxicity resolved after treatment with ILE therapy. Sodium bicarbonate has demonstrated efficacy in reversing QRS prolongation and cardiotoxicity following overdoses of tricyclic antidepressant [5] and other sodium channel blockers, but it was ineffective in these two cases.…”
Section: Case Discussionmentioning
confidence: 99%
“…Concerning amitriptyline intoxication, 50 mg/ kg is the lowest ingestion associated with mild toxicity and 15 mg/kg corresponds to the lowest dose associated with death. A single case of 325 mg (16 mg/kg) nortriptyline ingestion by a 4-year-old resulted in severe toxicity [7]. One fatal case of acute malicious exposure to amitriptyline of a 3-year-old was reported to the Annual report of the American Association of Poison Control Centers in 2002.…”
Section: What Do We Know About Amitriptyline Intoxication?mentioning
confidence: 99%
“…One fatal case of acute malicious exposure to amitriptyline of a 3-year-old was reported to the Annual report of the American Association of Poison Control Centers in 2002. The blood analyses revealed that the dosage of amitriptyline was: 4.600 µg/L and nortriptyline: 2.900 µg/L [7].…”
Section: What Do We Know About Amitriptyline Intoxication?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertonic sodium solutions are widely accepted as an antidote in systemic poisoning with non local-anaesthetic agents characterised by antagonism of fast-gated sodium ion channels [14,15]. Many psychotropic agents (tricyclic antidepressants for example) frequently taken in overdose share with bupivacaine both sodium channel blockade as a significant component of the toxicity and elevated lipophilicity [16].…”
mentioning
confidence: 99%